Effect of empagliflozin as add-on therapy on transtubular potassium concentration gradient in patients with type 2 diabetes hospitalized for acute decompensated heart failure. (25th November 2020) - Tamaki, S; Yamada, T; Watanabe, T; Morita, T; Furukawa, Y; Kawasaki, M; Kikuchi, A; Kawai, T; Seo, M; Abe, M; Nakamura, J; Yamamoto, K; et al.
Abstract: Background: The transtubular potassium concentration gradient (TTKG) has been reported to be a marker of renal aldosterone bioactivity, and has been shown to be a surrogate of arterial underfilling in patients with acute decompensated heart failure (ADHF). Moreover, high TTKG at discharge has been shown to be associated with poor prognosis in ADHF patients. Empagliflozin, one of the sodium glucose cotransporter 2 inhibitors, has been shown to reduce the risk of cardiovascular mortality in patients with type 2 diabetes mellitus (T2D) and cardiovascular disease. However, little is known about the effect of empagliflozin as add-on therapy on TTKG in T2D patients with ADHF. Purpose: We sought to elucidate the effect of empagliflozin as add-on therapy on TTKG in T2D patients with ADHF. Methods: We enrolled 58 consecutive T2D patients admitted for ADHF. On admission, enrolled patients were randomly assigned in a 1:1 ratio to either empagliflozin add-on therapy (EMPA(+)) or conventional glucose-lowering therapy (EMPA(−)). All patients in EMPA(+) group received empagliflozin (10 mg/day) throughout the study period. Left ventricular ejection fraction (LVEF) was measured at baseline using echocardiography. Body weight and vital signs, such as blood pressure and heart rate, were measured, and blood and urine samples were collected at baseline and 1, 2, 3 and 7 days after randomization. The TTKG was measured using the first morning urine samples collected on each day. TTKG was calculated according to the following equation: TTKG = (Ku/Ks)×(plasma osmolality/urine osmolality), where Ku is urine potassium concentration and Ks is serum potassium concentration, as previously reported. Results: Thirty patients were assigned to the EMPA(+) group, and 28 patients were assigned to the EMPA(−) group. There were no significant baseline differences in LVEF, plasma B-type natriuretic peptide (BNP) level, body mass index, or serum creatinine level between the EMPA(+) and EMPA(−) groups. TTKG did not significantly differ between the two groups at baseline. However, seven days after randomization, plasma BNP level was significantly lower in the EMPA(+) group than in the EMPA(−) group (median 227 [IQR 114–381] pg/mL vs 362 [227–554] pg/mL, p=0.0294). Furthermore, TTKG of the EMPA(+) group was significantly lower at 2, 3 and 7 days after randomization (Figure). Conclusions: This study demonstrated that empagliflozin as add-on therapy can lower TTKG in T2D patients with ADHF. Funding Acknowledgement: Type of funding source: None